Proximity is a Social Process - A Conceptual Framework. - Anja Dettmann; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2010)
Spatial proximity is assumed in the literature to be a prerequisite and trigger for cooperation and, subsequently, innovation. This paper examines conceptually the role of proximity between actors for cooperation activities. Using theories and findings from social psychology and combining them with geographical issues, it provides new insights into the emergence and development of professional collaborative relationships and the role that spatial proximity plays. Thereby the paper stays on the level of individuals (micro-level) and explains how the willingness to collaborate emerges and how local partner priorities are developed.
Keywords: L14; O32; R10; 330; Collaboration; Partner Choice; Proximity; Innovation; Geography